2017
DOI: 10.13075/ijomeh.1896.00851
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electromagnetic radiation emitted by monitors on changes in the cellular membrane structure and protective antioxidant effect of vitamin A – In vitro study

Abstract: Objectives: The increasing number of devices emitting electromagnetic radiation (EMR) in people's everyday life attracted the attention of researchers because of possible adverse effects of this factor on living organisms. One of the EMR effect may be peroxidation of lipid membranes formed as a result of free radical process. The article presents the results of in vitro studies aimed at identifying changes in malondialdehyde (MDA) concentration -a marker of lipid peroxidation and antioxidant role of vitamin A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Dear Editor, With great enthusiasm I read the paper authored by Lewicka et al entitled "Impact of electromagnetic radiation emitted by monitors on changes in the cellular membrane structure and protective antioxidant effect of vitamin A -In vitro study" [1]. Authors of this paper had evaluated the effect of electromagnetic radiation (1 kHz frequency, 220 V/m electric field) emitted by liquid-crystal-display (LCD) monitors on the concentration of malondialdehyde (MDA) as a marker of lipid peroxidation.…”
Section: Concerning the Paper "Impact Of Electromagnetic Radiation Emmentioning
confidence: 99%
See 2 more Smart Citations
“…Dear Editor, With great enthusiasm I read the paper authored by Lewicka et al entitled "Impact of electromagnetic radiation emitted by monitors on changes in the cellular membrane structure and protective antioxidant effect of vitamin A -In vitro study" [1]. Authors of this paper had evaluated the effect of electromagnetic radiation (1 kHz frequency, 220 V/m electric field) emitted by liquid-crystal-display (LCD) monitors on the concentration of malondialdehyde (MDA) as a marker of lipid peroxidation.…”
Section: Concerning the Paper "Impact Of Electromagnetic Radiation Emmentioning
confidence: 99%
“…Another major shortcoming comes from the distance between the samples and the source of electromagnetic radiation. Lewicka et al [1] state that "Preserving constant conditions of the environment the preparation was exposed to the activity of the electromagnetic field of 1 kHz frequency and 220 V/m intensity (corresponding to a distance of 15 cm from the monitor) for 30 min and 60 min." According to the Occupational Safety and Health Administration (OSHA), the preferred viewing distance from the eye to the front surface of the computer screen is 50-100 cm (20-40 inches) [3].…”
Section: Concerning the Paper "Impact Of Electromagnetic Radiation Emmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, I am writing in response to the letter to the Editor [1] concerning the paper entitled "Impact of electromagnetic radiation emitted by monitors on changes in the cellular membrane structure and protective antioxidant effect of vitamin A -In vitro study" [2]. This paper has evaluated the effect of electromagnetic radiation (1 kHz frequency, 220 V/m intensity) emitted by liquid-crystal-display (LCD) monitors on the concentration of malondialdehyde (MDA) that is a marker of lipid peroxidation.…”
Section: Authors' Response (September 1 2017) To the Letter To The Ementioning
confidence: 99%
“…Increasingly promising researches indicated that natural products, especially with potent antioxidant activity, displayed effective protection against electromagnetic radiation. 14,15 However, there is still a lack of protective agents with definite and unique mechanisms for microwave-induced cognitive damage.…”
Section: Introductionmentioning
confidence: 99%